PENGARUH VARIASI MEDIA PENDINGIN TERHADAP KEKERASAN DAN STRUKTUR MIKRO HASIL REMELTING AL-SI BERBASIS LIMBAH PISTON BEKAS DENGAN PERLAKUAN DEGASSING - Mu?afax, Ferdiaz Dinov (Jurnal Nosel, 2013)
The purpose of this study was (1) Determine the effect of the variation media cooling to hardness remelting of Al-Si based used piston waste with degassing treatment, (2) Determine the effect of the variation cooling media to micro structure remelting of Al-Si based used piston waste with degassing treatment, (3) Determine the effect of the optimal cooling media results hardness and micro structure remelting of Al-Si based used piston waste with degassing treatment.This study used an experimental method that uses a single independent variable factor (media cooling variation) and two-factor variable (hardness and microstructure). Objects in this study using the results of remelting of Al-Si piston former waste. Data analysis techniques in this study using descriptive data analysis results graphically illustrate the tables and histograms as well as images of micro structures. Input parameters in analyzing the data include: variations in the cooling medium (water well, oil SAE 40 and salt liquid), micro structure, and hardness.The results showed a change in the level of hardness and the micro structure formed. From the hardness test results obtained the highest level of hardness in the media cooling well water 86.83 BHN respectively towards the lows of the cooling medium salt liquid at 83.63 BHN, media SAE 40 oil cooler for 63.24 BHN, and the non-quenching at low 54.22 BHN. Microstructure test shows the micro structure consists of the formation of Al that is soft (low hardness) and Si as an addition to the level of hardness that affect resilience, the size of the grains of different suggesting that different levels of hardness coupled. So we get the greater amount Si then the resulting hardness will increase.